Protection for Sale with Imperfect Rent Capturing - Giovanni Facchini; Johannes van Biesebroeck; Gerald Willmann (Kiel University, Department of Economics, 2003)
We extend the protection for sale framework by modelling non tariff barriers. Explicitly introducing partial rent capturing leads to a testable specification that bridges the gap between the theoretical Grossman and Helpman (1994) model and its empirical implementation, where coverage ratios have been used to measure protection. Our econometric analysis supports the augmented specification and leads to more realistic estimates for the structural parameters of the model.
urn:nbn:de:101:1-200910201104
Keywords: F13; 330; Protektionismus; Interessenpolitik; Public Choice; Rent Seeking; Schätzung; Theorie; Welt